Global Health Partnerships for Continuing Medical Education: Lessons from Successful Partnerships. Issue 3 (2nd July 2016) - Sriharan, Abi; Harris, Janet; Davis, Dave; Clarke, Mike
Abstract: The past decade has witnessed an increase in global partnerships created to strengthen health systems and provide training to health professionals in low- and middle-income countries. These partnerships are complex interventions. This study focused on unpacking the characteristics of global partnerships that provide continuing education for health professionals. A realist approach underpinned the research design to identify the mechanisms that shape successful global partnerships. Two case studies focusing on global continuing medical education (CME) were studied longitudinally using a realist evaluation approach. To complement that finding, published research reports of global CME partnerships were synthesized using a realist synthesis approach. Data were collected over a three-year period and included interviews, participant observations, document reviews, and surveys. A hybrid thematic approach guided the data analysis. The study results suggested that global CME partnerships are highly dependent on human factors. On the one hand, motivational factors related to individual players help to shape the partnership goals, directions, and outcomes. On the other hand, relational factors such as trust, communication, and understanding play a key role in developing and sustaining global partnerships. As such, these partnerships highly rely on the individuals who champion the partnership at the country level or at the partnership level and in their ability to build relationships as well as empower key stakeholders.